Concordato y jurisprudencia constitucional en Colombia (2005)
Colombian State and the City of Vatican have signed a pact, called “Concordato” a long time ago. The last reform of this international pact was accepted by Colombian law in 1974, twenty years before the Colombian new Constitution reform signed in 1991. Therefore the validity of the international pact between Colombian State and the Vatican can not be unknown by the Constitutional Court, established by the new Colombian Constitution. Nevertheless the Court has decided against the constitutionality of the “Concordato”.